Regulating Free Movement of Goods within the European Union - Berlingher, Daniel (Journal of Legal Studies, 2018)
The principle of the free movement of goods in one of great importance for the European Union and for in general and for the Internal Market and the European citizens in particular. Starting from the fact that the Internal market is considered to be a critical element for the present and future prosperity of the European Union in a globalized world, the objective of the present text is to present and analyse, in a concise manner, the main legal provisions that govern this field. In order to accomplish this objective we made reference to the following aspects: considerations regarding the role and importance of the free movement of goods in the European internal market; the role of the European Commission within the internal market and implicitly for the free movement of goods; Treaty provisions governing the free movement of goods; and related instruments of secondary law related to the free movement of goods.